High-throughput functional screen of mouse gastrula cDNA libraries reveals new components of endoderm and mesoderm specification - Chiao, Eric; Leonard, Jeff; Dickinson, Kari; Baker, Julie C.

(untitled) (Genome Research, 2005)
This study describes a cross-species functional screen of mouse gastrula cDNA libraries for components of endoderm and mesoderm specification. Pools of 96 cDNAs from arrayed mouse gastrula cDNA libraries were transcribed into mRNA and injected into either the presumptive mesoderm or the ectoderm of one-cell Xenopus laevis embryos. Injected embryos were examined at gastrula stage by in situ hybridization with endoderm or mesoderm markers. Using this approach, we screened over 700 pools or ∼60,000 cDNAs. We identified 17 unique cDNAs that function during mesoderm and/or endoderm specification and 16 that cause general morphology changes. Identified molecules fall into eight general functional groups as follows: cell cycle components (seven), transcription factors (four), extracellular secreted molecules (seven), transmembrane receptors (one), intracellular signaling components (five), microtubule components (two), metabolism molecules (three), and unknown (four). Several of the genes we identified would not have been predicted to be involved in endoderm or mesoderm specification, highlighting the usefulness of nonbiased screening approaches. This includes Otx2, which we show is a downstream target of Xsox17β. The speed, low cost, and high efficiency of this cross-species screen makes it an ideal method for examining cDNAs from difficult-to-obtain sources. Therefore, this approach complements the current mouse molecular genetics systems and provides a powerful means for the genome-wide examination of mammalian gene function.